Analisis Perkembangan Sosial Pada Anak Bilingual di Abad 21 - Aulia Annisa (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2021)
Communication is an important requirement in order to adapt to the broad social environment in the 21st century. One of the efforts made is the use of two languages (bilingual) in everyday life. However, parents unconsciously put children into a world with language development tasks that are more complex than the competencies that children should have. This of course will affect social development and children's ability to interact with the environment. This study analyzes the use of bilinguals in terms of children's social competence and social behavior. The research method uses literature studies by analyzing 20 books and scientific articles related to bilingualism and children's social development. The data analysis technique used content analysis related to the phenomena, causes and effects of social development in children using bilinguals. The results of the analysis show that the use of bilingual children has a positive and negative side to the child's social development. The positive thing is that bilingual children can easily adapt outside their social environment as a means of communication. There will be a sense of pride in the child because he can master more than one language. But the negative thing is, some of the bilingual children will find it difficult to understand new concepts in a different language, so they often feel depressed. In addition, there is a gap between children and their social environment.